A Case of Anal Fistula Treated by Individualised Homoeopathic Medicine (Advancements in Homeopathic Research, 2022)
Anal fistula is one of the commonest problems to encounter in clinical practice. In conventional system of medicine, medication has a very limited role and surgery is the only option. This is the case of a patient presented with pain, offensive discharge and itching near anus for last three months. Afterwards he was diagnosed as a case of anal fistula on the basis of peculiar history and physical examinations. Treatment was started prospectively following strict homoeopathic principles and follow-ups done in suitable intervals for about 4months. A marked improvement was noted in the course of the treatment. Rationale of the case report is to show the effective management of such cases with proper homoeopathic treatment.
Keywords: Anal fistula; Homoeopathy